Urinary liver-type fatty acid binding protein is an independent predictor of stroke and mortality in individuals with type 1 diabetes - Panduru, Nicolae; Bierhaus, Angelika; Humpert, Per Magnus (Diabetologia, 2017)
Aims/hypothesis: In type 1 diabetes, cardiovascular disease (CVD) and diabetic nephropathy progress in parallel, thereby potentiating the risk of premature death during their development. Since urinary liver-type fatty acid binding protein (L-FABP) predicts the progression of diabetic nephropathy, the aim of this study was to investigate whether urinary L-FABP also predicts cardiovascular outcomes and mortality.MethodsWe tested our hypothesis in a Finnish cohort of 2329 individuals with type 1 diabetes and a median follow-up of 14.1 years. The L-FABP to creatinine ratio was determined from baseline urine samples. The predictive value of urinary L-FABP was evaluated using Cox regression models, while its added predictive benefit for cardiovascular outcomes and mortality was evaluated using a panel of statistical indexes.ResultsUrinary L-FABP predicted incident stroke independently of traditional risk factors (HR 1.33 [95% CI 1.20, 1.49]) and after further adjustment for eGFR (HR 1.28 [95% CI 1.14, 1.44]) or AER (HR 1.24 [95% CI 1.06, 1.44]). In addition, it predicted mortality independently of traditional risk factors (HR 1.34 [95% CI 1.24, 1.45]), and after adjustment for eGFR (HR 1.29 [95% CI 1.18, 1.39]) or AER (HR 1.22 [95% CI 1.09, 1.36]). Urinary L-FABP was as good a predictor as eGFR or AER, and improved the AUC for both outcomes on top of traditional risk factors, with no reclassification benefit (integrated discrimination improvement/net reclassification improvement) for stroke or mortality when AER or eGFR were added to traditional risk factors. However, urinary L-FABP was not a predictor of other cardiovascular endpoints (coronary artery disease, peripheral vascular disease and overall CVD events) when adjusted for the AER.Conclusions/interpretationUrinary L-FABP is an independent predictor of stroke and mortality in individuals with type 1 diabetes.